THE EFFECT OF BUILDING INFORMATION MODELLING (BIM) METHOD IMPLEMENTATION ON THE EFFECTIVENES OF BUILDING CONSTRUCTION IMPLEMENTATION MANAGEMMENT IN THE CONSTRUCTION INDUSTRY - Siregar, Immanuel Simon Zevanya; Simanjuntak, Pinondang; Purnomo, Candra Christianti (LPPM Universitas Negeri Jakarta, 2024)
The aim of this study is to analyze the impact of Building Implementation Information Modeling (BIM) on the efficiency of building construction management quantitatively. It has become a significant method in the construction industry with the potential to improve collaboration, coordination and information management in the implementation of construction projects. The research method uses simple linear regression analysis with data from construction professional respondents. The study involved 52 contractor companies in the construction industry. The selection of these samples is aimed at obtaining representative and adequate data for simple linear regression analysis. With large sample sizes, the results are expected to be more accurate and reliable. In addition, the selection of 52 respondents is also carried out to cover a variety of perspectives and professional experience of construction, making the data obtained more representative, and more reliable for the analysis performed. Implementation of BIM has a significant and positive impact on building construction management, demonstrated by a count t value = 12.217 greater than the table t value of 2.00856. The determination coefficient (R-square) of 0.749 or 74.9% suggests that 74.9 percent variation in building management efficiency can be explained by the implementation of BIM. This finding emphasizes the importance of using BIM to improve management effectiveness in building construction in the construction industry. The implications of this research provide a basis for encouraging the adoption of BIM as an effective tool in the management of construction projects.